Quantitative Evaluation of the Effectiveness of Chemical Peelings in Reducing Acne Lesions Based on Gray-Level Co-Occurrence Matrix (GLCM) - Odrzywołek W; Deda A; Zdrada J; Wilczyński S; Błońska-Fajfrowska B; Lipka-Trawińska A (Dove Medical Press, 2022)
Wiktoria Odrzywołek,1 Anna Deda,2 Julita Zdrada,1 Sławomir Wilczyński,1 Barbara Błońska-Fajfrowska,1 Aleksandra Lipka-Trawińska1 1Department of Basic Biomedical Science, Faculty of Pharmaceutical Sciences in Sosnowiec, Medical University of Silesia, Katowice, Poland; 2Department of Cosmetology, Faculty of Pharmaceutical Sciences in Sosnowiec, Medical University of Silesia, Katowice, PolandCorrespondence: Wiktoria Odrzywołek, Department of Basic Biomedical Science, Faculty of Pharmaceutical Sciences in Sosnowiec, Medical University of Silesia, 41-200 Sosnowiec, ul. Kasztanowa 3, Katowice, Poland, Tel +32269 98 30, Email wiktoria.odrzywolek@wp.plPurpose: Acne vulgaris is a chronic, inflammatory disease accompanied by lesions affecting the structure of the skin. Chemical peels are one of the methods of reducing acne vulgaris. There is still a lack of quantitative methods of assessing impact of cosmetic procedure on the skin. Skin condition depends on skin texture characterization; therefore, the analysis that provides data about the textures can be helpful in assessing the effectiveness of cosmetic treatments.Patients and Methods: The study involved 24 volunteers with acne lesions. Each participant underwent 4 treatments using chemical peels at two-week intervals. Before, during and after procedure clinical photography were made. To assess effectiveness of chemical peeling in acne lesion reduction, we were used gray-level co-occurrence matrix (GLCM) analysis. Qualitative assessment of acne severity was made by 12 experts in dermatology.Results: After a series of treatments, the GLCM contrast value decreased in each area of the face, and the GLCM homogeneity value increased, which means that the number of acne lesions was reduced. Expert assessment according to the IGA scale confirms the effectiveness of therapy with both salicylic and glycolic acid and pyruvic acid.Conclusion: The results of this study prove that GLCM analysis is a useful tool for assessing the effectiveness of chemical peel treatments. It can also be used for quantitative assessment of skin texture.Keywords: gray-level co-occurrence matrix, acne, chemical peelings, acne treatment, skin texture